The Role of Artificial Intelligence in Improving the Efficiency of Financial Risk Management - Utomo, Widodo Budi; Yaqin, Nurul; Sari, Nurmala (Doctoral Program of Social Science Pasundan University, 2025)
Artificial Intelligence (AI) has revolutionized the financial sector by offering sophisticated solutions for financial risk management. This article discusses how AI helps companies improve efficiency in identifying, managing, and minimizing risks in the financial sector, including market, credit, and operational risks. With algorithms such as machine learning, natural language processing, and neural networks, AI can process big data quickly, provide accurate analysis, and support strategic decision-making. Despite challenges such as data security and context understanding, the benefits of AI go far beyond these barriers, making it an essential innovation in the digital age. This research highlights the importance of AI integration to create a more secure, efficient, and competitive financial system.